Cardiac Myxomas Show Elevated Native T1, T2 Relaxation Time and ECV on Parametric CMR - Nasser, Sarah B.; Doeblin, Patrick; Doltra, Adelina; Schnackenburg, Bernhard; Wassilew, Katharina; Berger, Alexander; Gebker, Rolf; Bigvava, Tamuna; Hennig, Felix; Pieske, Burkert; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2020)
Introduction: While cardiac tumors are rare, their identification and differentiation has wide clinical implications. Recent cardiac magnetic resonance (CMR) parametric mapping techniques allow for quantitative tissue characterization. Our aim was to examine the range of values encountered in cardiac myxomas in correlation to histological measurements. Methods and Results: Nine patients with histologically proven cardiac myxomas were included. CMR (1.5 Tesla, Philips) including parametric mapping was performed in all patients pre-operatively. All data are reported as mean ± standard deviation. Compared to myocardium, cardiac myxomas demonstrated higher native T1 relaxation times (1554 ± 192 ms vs 1017 ± 58 ms, p < .001), ECV (46.9 ± 13.0 % vs. 27.1 ± 2.6 %, p = .001) and T2 relaxation times (209 ± 120 ms vs. 52 ± 3 ms, p = .008). Areas with LGE showed higher ECV than areas without (54.3 ± 17.8 % vs. 32.7 ± 18.6 %, p = .042), with differences in native T1 relaxation times (1644 ± 217 ms vs. 1482 ± 351 ms, p = .291) and T2 relaxation times (356 ± 236 ms vs. 129 ± 68 ms, p = .155) not reaching statistical significance. Conclusions: Parametric CMR showed elevated native T1 and T2 relaxation times and ECV values in cardiac myxomas compared to normal myocardium, reflecting an increased interstitial space and fluid content. This might help in the differentiation of cardiac myxomas from other tumor entities.